1995
DOI: 10.1111/j.1574-6968.1995.tb07554.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a bacterium which utilizes polyester polyurethane as a sole carbon and nitrogen source

Abstract: Various soil samples were screened for the presence of microorganisms which have the ability to degrade polyurethane compounds. Two strains with good polyurethane degrading activity were isolated. The more active strain was tentatively identified as Comamonas acidovorans. This strain could utilize polyester-type polyurethanes but not the polyether-type polyurethanes as sole carbon and nitrogen sources. Adipic acid and diethylene glycol were probably the main degradation products when polyurethane was supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(75 citation statements)
references
References 8 publications
1
72
0
2
Order By: Relevance
“…It has been found that polyurethane foams prepared from liquefied cellulose, bark and starch can be degraded in soil (Hatakeyama 1996;Ge et al 2000;Lee et al 2002). It has been also reported that synthetic polyester-type polyurethane foams are decomposed by a number of fungi and bacteria (Daby and Kaplan 1968;Crabbe et al 1994;Nakajima-Kambe et al 1995), and this degradation is generally initiated by hydrolysis of the ester bond with hydrolytic enzymes such as esterase. Many groups reported the purification and characterization of those enzymes (Pathirana and Seal 1984;Kay et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that polyurethane foams prepared from liquefied cellulose, bark and starch can be degraded in soil (Hatakeyama 1996;Ge et al 2000;Lee et al 2002). It has been also reported that synthetic polyester-type polyurethane foams are decomposed by a number of fungi and bacteria (Daby and Kaplan 1968;Crabbe et al 1994;Nakajima-Kambe et al 1995), and this degradation is generally initiated by hydrolysis of the ester bond with hydrolytic enzymes such as esterase. Many groups reported the purification and characterization of those enzymes (Pathirana and Seal 1984;Kay et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological features documented previously by Kilb et al (2003) suggests that A. facilis is a common water contaminant due its ability to swarm (spread), colonise, and flourish rapidly in a mineral medium with or without any organic matter (Palleroni 1989). This suggests either A. facilis is able to grow chemolithotrophically, or the polyurethane plastic tubing components were leaching out as a supply of nutrients supporting its survival and proliferation (Nakajima-Kambe et al 1995). The next colonizer in the one to 14 days was the Gram negative L. cholodnii, a filamentous, sheathed, bacterium that can form globules of poly-hydroxybutyrate in their cytoplasm as a food reserve.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparing the different results given by each researcher is very difficult because the PU type and the microorganism type are different for each study. Many reports can be found on PU biodegradation in the laboratory under controlled conditions, especially on biodegradation of polyester PU by microorganisms (the main attention has been devoted to fungi) [13]. The literature results mostly come from lab studies, in many cases, providing additional nutrients to microorganisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The composition of the basal medium used is described by Nakajima-Kambe et al [13], where glucose and/or ammonium nitrate are omitted when PU is supplied as a sole carbon and/or nitrogen source (Table 8.1), respectively.…”
Section: Microbial Growth Mediamentioning
confidence: 99%